PERLINDUNGAN HUKUM TERHADAP PENCIPTA LAGU YANG KARYANYA DIMANFAATKAN OLEH PELAKU USAHA KARAOKE - Sattwika Yudharma Sutha, Gede; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 02, Januari 2015, 2015)
Copyright applies in all areas of one's life is the art of music. The songs are already registered should get royalties when used for commercial purposes, one of the businesses that are often violated karaoke businesses. The purpose of this paper is to explain the legal protection of songwriter whose work is used by businesses and sanctions against the perpetrators karaoke karaoke businesses that do not have a license to a copyrighted work. Judging from his goal, this paper uses the method of normative legal research with this type of approach legislation. Sources of law derived from statutes and law books. In conclusion, all forms of legal protection against sanctions for violations song and its use is governed in the Copyright Act.
Keywords: Protection, Creator, Song, Karaoke Business